2008
DOI: 10.1111/j.1399-6576.2007.01558.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients with PTSD after intensive care avoid hospital contact at 2‐year follow‐up

Abstract: Patients withPost-traumatic Stress Disorderafter intensive care avoid hospital contact at 2-year follow-u

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…That is, because prior psychiatric illness is a potent predictor of PTSD given trauma, the prevalence estimates here are likely underestimates for the general population of ARDS survivors. In addition, it is clear that PTSD symptoms in ICU survivors sometimes affect willingness to participate in follow-up research (i.e., patients with PTSD often avoid hospitals or medical visits, so estimates of prevalence could also be low for this reason) [27]. Not surprisingly, post-ARDS PTSD was associated with substantially worse HRQOL [16].…”
Section: Prevalence Of Post-intensive Car Unit Post-traumatic Stress mentioning
confidence: 98%
“…That is, because prior psychiatric illness is a potent predictor of PTSD given trauma, the prevalence estimates here are likely underestimates for the general population of ARDS survivors. In addition, it is clear that PTSD symptoms in ICU survivors sometimes affect willingness to participate in follow-up research (i.e., patients with PTSD often avoid hospitals or medical visits, so estimates of prevalence could also be low for this reason) [27]. Not surprisingly, post-ARDS PTSD was associated with substantially worse HRQOL [16].…”
Section: Prevalence Of Post-intensive Car Unit Post-traumatic Stress mentioning
confidence: 98%
“…It is in this sense that post-traumatic stress disorder (PTSD) has been studied in hospital settings, preferably in critical areas such as emergency and intensive care due to the emotional consequences, the memories of being hospitalized and the suffering reported by the patient after an ICU experience (Capuzzo et al, 2008;Löf, Ahlströn, & Berggren, 2006;Ringdal, Plos, Lundberg, Johansson, & Bergbom, 2009;Roberts, Rickard, Rajbhandari, & Reynolds, 2007). PTSD is considered an anxiety disorder precipitated by a trauma and its development is associated with an external traumatic event source (Kristensen, 2005).…”
mentioning
confidence: 99%
“…This literature review has indicated that ICU diaries are a low cost, grass roots initiative which have demonstrated potential therapeutic benefit in a population recognised to be at significant risk of psychological morbidity (Capuzzo et al . , Jackson et al . , Peris et al .…”
Section: Discussionmentioning
confidence: 99%